Characteristic of Bioorganic Component of Municipal Solid Waste - V. Y. Prykhodko; K. P. Hiulakhmedova (Вісник Харківського національного університету імені В.Н. Каразіна: Серія Екологія, 2018)
Purpose. Characteristics of the easily decomposed organic municipal solid waste flow: evaluation of composition, main components content and determination of possible recycling directions. Methods. System analysis methods, statistical processing of data were used. Results. Almost 60% of the municipal solid waste mass was composed of components containing biodegradable carbon – food and garden wastes, paper and cardboard, textiles, nappies, rubber and leather, wood. The total content and correlation between the main components depend on local conditions and change over time. The coefficient of variation was chosen as a criterion for assessing the variability of the content of individual components in the MSW total mass. It was shown that the most variable was the content of rubber and leather, as well as wood; the most stable characteristic was the content of food waste. The municipal solid waste management practice is to dispose of easily decomposed organic waste into landfill and dumps, which are sources of environmental pollution by e.g. greenhouse gases. The exception is some part of paper and cardboard. Given the obtained characteristics of wastes containing biodegradable carbon, we present the main directions of its recycling that are possible today. Conclusions. A group of wastes containing biodegradable carbon constitutes a significant proportion of MSW. The correlation between the different components of this group is a characteristic feature of the generation source and should be taken into account by developing an effective system of waste management for a particular city or region. The current waste management practice leads to waste disposal into landfill and dumps, which are sources of environmental pollution. On the other hand, such waste can be efficiently recovered, especially the largest by weight food, garden waste and paper and cardboard. However, a necessary condition for this purpose is their separation from the general municipal solid waste stream in the moment of waste generation.